1998
DOI: 10.1016/s0886-3350(98)80109-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative method to determine the cohesion of viscoelastic agents by dynamic aspiration

Abstract: The method provided a quantitative basis for the clinical classification of viscoelastic materials as cohesive or dispersive. The aspiration kinetics profile (curve shape), maximum rate of removal, and vacuum levels at which the bolus removal of the viscoelastic agent started (break point) were useful in characterizing the viscoelastic agents. Because the results agree with the clinical impression of cohesion/dispersion, this method may be used to predict the surgical performance of viscoelastic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…The method developed by Poyer et al 10 is useful in measuring the cohesive properties of HA, as it is fast and simple. The purpose of our study was to determine the effect of concentration and molecular weight on the cohesive properties of HA and to determine which dynamic rheological parameters (commonly measured theological parameters) correlate best with the cohesion of HA solutions as measured using the method of Poyer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The method developed by Poyer et al 10 is useful in measuring the cohesive properties of HA, as it is fast and simple. The purpose of our study was to determine the effect of concentration and molecular weight on the cohesive properties of HA and to determine which dynamic rheological parameters (commonly measured theological parameters) correlate best with the cohesion of HA solutions as measured using the method of Poyer.…”
Section: Discussionmentioning
confidence: 99%
“…The cohesion-dispersion index (CDI) was measured by using an apparatus built according to the description in a paper by Poyer et al 10 A schematic of the apparatus used is shown in Figure 1. The principle of the technique is to measure the amount of sample aspirated with increasing vacuum applied to the sample; vacuum levels of 127, 254, 381, 533, and 711 mmHg were used.…”
Section: Cohesion-dispersion Indexmentioning
confidence: 99%
See 3 more Smart Citations